A primer on common supplements and dietary measures used by patients with inflammatory bowel disease - Hadi J Minhas; Konstantinos Papamichael; Adam S. Cheifetz; Robert J. Gianotti (SAGE Publishing, 2023)
Inflammatory bowel disease (IBD) is a chronic disease of the intestines. The pathophysiology of IBD, namely Crohn's disease and ulcerative colitis, is a complex interplay between environmental, genetic, and immune factors. Physicians and patients often seek complementary and alternative medicines (CAMs) as primary and supplementary treatment modalities. CAMs in IBD span a wide range of plants, herbs, pre/probiotics, and include formulations, such as cannabis, curcumin, fish oil, and De Simone Formulation. Dietary measures are also used to improve symptoms by attempting to target trigger foods and reducing inflammation. Examples include the specific carbohydrate diet, the Mediterranean diet, and a diet low in fermentable oligo-, di- and monosaccharides as well as polyols (FODMAP). We examine and review the most common complementary supplements and diets used by patients with IBD.